Genetic diversity among potato varieties (Solanum tuberosum L.) grown in Mexico, using RAPD and ISSR markers - Onamu, Rose; Legaria Solano, Juan Porfirio (Revista Mexicana de Ciencias Agrícolas, 2018)
A consensus analysis of RAPD and ISSR was used to study genetic diversity in fifteen potato cultivars (9 cultivars bred in Europe, N. America and Mexico, and 6 Mexican creole cultivars) grown in Mexico. Amplifications using five decamer primers randomly generated and five ISSR primers produced 138 bands, from which 116 (84.4%) were polymorphic. Cultivars Fianna and Armada showed the highest similarity coefficient (0.89). In contrast, Cambray Rose Tollocan and Morelos had the lowest similarity coefficient (0.55). High genetic differentiation among cultivars (GST= 0.71) and low gene flow (Nm= 0.19) across all loci, indicated high genetic divergence among the 15 cultivars. Analysis of molecular variance (AMOVA) revealed a significant contribution of differences among regions, among cultivars, among and within populations to the overall diversity of potato cultivars studied. Consensus data on RAPD and ISSR markers were very useful to study genetic diversity and population structure in potato cultivars.